Development of scientific approach-based interactive multimedia for elementary school dyscalculia children - Firda Alfiana Patricia; Kenys Fadhilah Zamzam (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
Difficulties in learning Mathematics for children are rarely understood by parents, even parents sometimes do not understand dyscalculia for children. In fact, dyscalculia children need special motivation and guidance. Interactive multimedia can be used as an alternative in giving special guidance for dyscalculia children. The objective of developing this interactive multimedia was to produce a product for elementary school dyscalculia children using android application suitable for a scientific approach. This development research employed four-D models development model which was developed by Thiagarajan. In this design, the researchers tested the validity level, practicality level, and also the effectiveness of the developed multimedia. The research subject was elementary school dyscalculia children especially the third graders. Based on the result of the validity test conducted by three validators, it was shown that the overall average was 3.20 where it was categorized as valid to be used. The result of the practicality test showed that the overall average was 3.09 where it was categorized as practical to be used. The result of effectiveness test showed that the overall average was 3.36 where it was categorized as effective to be used. The conclusion of this research was that the developed scientific approach-based interactive multimedia was practical and effective to be used as a learning source.